Development of an image processing algorithm (IPA‐Delfin) for the digital reconstruction of composite overwrapped pressure vessels - Rozo Lopez, Nicolas; Tao, Yuchen; Çelik, Hakan; Hopmann, Christian (Polymer composites, 2023)
Wet filament winding has been established as the primary manufacturing process for overwrapped pressure vessels. However, the prediction of the mechanical performance of pressure vessels is still not sufficiently accurate, mostly due to process‐induced deviations within the laminate structure. In this work, we present an image processing algorithm (IPA‐Delfin) that enables the real‐time generation of a digital reconstruction based on the actual geometry and position of the placed roving. A Type‐IV pressure vessel is analyzed under real manufacturing conditions. Our approach allows the measurement of the overlapping degree of roving within the laminate and the prediction of gaps. The results show that the fiber‐band width and the overlapping area vary significantly when the roving is placed directly on the vessel's polymer liner. A more constant and uniform fiber‐band width and overlapping area were observed when the filament winding took place on the previously placed roving. Hence, the IPA‐Delfin can be potentially used for the generation of digital twins of composite overwrapped pressure vessels. The laminate layers of Type‐IV pressure vessel are analyzed using an image processing algorithm (IPA‐Delfin) and under real manufacturing conditions. The algorithm enables the real‐time generation of a digital reconstruction based on the actual geometry and position of the placed roving.